2000
DOI: 10.1051/limn/2000003
|View full text |Cite
|
Sign up to set email alerts
|

The Leptophlebiidae : Atalophlebiinae of New Caledonia (Ephemeroptera). Part VII : Systematics

Abstract: The seventh in a series on the Leptophlebiidae O^phemeroptera) of New Caledonia, this papers treats three new genera (Paraluma, Oumas, and Amoa) and 12 new species. For Paraluma gen.n., the type species P. cancellata sp.n., P. triangularis sp.n., P. gilva sp.n. and P. minuta sp.n. are described from male and female imagos and nymphs, P. pulla sp.n. from male imagos and nymphs, and P. maculata sp.n. from male and female imagos. For Amoa gen.n., the type species A. fronini sp.n., A. subsolano sp.n. and A. orthog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…The only exceptions were two adult specimens of the baetid genus Pseudocloeon (?) found in Rivière Bleue ( Peters et al 1978 ). However, no further specimens of Baetidae have been collected from this area since then, and the occurrence of this family in New Caledonia is therefore doubtful.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The only exceptions were two adult specimens of the baetid genus Pseudocloeon (?) found in Rivière Bleue ( Peters et al 1978 ). However, no further specimens of Baetidae have been collected from this area since then, and the occurrence of this family in New Caledonia is therefore doubtful.…”
Section: Introductionmentioning
confidence: 89%
“…The research on the mayflies in New Caledonia has been led by William L. Peters and Janice G. Peters, who published a series of eight articles focusing on taxonomy and systematics ( Peters et al 1978 ; Peters and Peters 1980 , 1981a , b , 2000 ; Peters et al 1990 , 1994 ; Peters and Mary 2016 ). New Caledonian mayflies belong to a single family Leptophlebiidae and subfamily Atalophlebiinae ( Peters 2001 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…G2 occur only in peridotitic lands. PETERS et al (1978) and CHAZEAU (1994) suggested a specific endemism of fauna to ultramafic rocks. For example, PETERS et al (1978) examined the distribution of Ephemeroptera Leptophlebiidae Lepeorus over La Grande Terre and showed that the subspecies Lepeorus calidus notialis and L. goyi australis were restricted to the ultramafic South region of La Grande Terre, whereas the subspecies Lepeorus calidus calidus and L. goyi goyi occur everywhere else.…”
Section: Spatial Variationmentioning
confidence: 99%
“…Part I of this series lists all localities (Peters et al, 1978). Other works are Peters and Peters (1980, 1981a, 1981b, 2000 and Peters et al (1990Peters et al ( , 1994.…”
Section: Introductionmentioning
confidence: 99%